SIMILARITIES AND DIFFERENCES OF VOICE WHICH IS THE CATEGORY OF VERBS IN ENGLISH AND UZBEK LANGUAGES - Mashrafxo’jayeva Rayhona; Aziz Mukhamadiev (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: In linguistics, the term "voice" refers to a grammatical category of verbs that indicates the relationship between the subject and the action expressed by the verb. There are typically two primary voices in many languages: active and passive. Understanding and utilizing voice in language helps convey information about the relationships between the entities involved in an action and can also affect the overall tone and emphasis of a sentence.